PERSEPSI MAHASISWA TENTANG REGULASI SERTIFIKASI HALAL JALUR SELF DECLARE PADA UMKM DI PEKANBARU - Sundari, Rina (Komunitas Manajemen Kompetitif, 2024)
Halal certification is the process of obtaining halal certification in accordance with Islamic law, the aim of which is to provide legal certainty about the halalness of a product so that it can reassure the minds of those who consume it. Researchers are interested in knowing how business actors can make implementing Halal Certification using the Self-Declaration Route easier or more difficult for MSMEs. And also, the self-declare route will only be available in 2022, so there is already quite a lot of research on halal certification, but there is no or not too much for the self-declare route, therefore researchers want to know more about self-declare. After the online questionnaire was distributed to 36 students, the results were regarding the halal application of 36 students, 47.2% said they didn't know, 41.7% said they knew and 11.1% said they were doubtful. Because this concerns technological advances, there is a need to socialize the Indonesian Ministry of Religion's Halal Product Guarantee Agency (BPJPH) in the context of implementing the Sihalal Application in the Regional Halal Services Task Force for MSMEs in Pekanbaru.